Innovation in Numeracy Learning Through Immersive Media for Pre-Service Teachers in Professional Education - Rohimah, Siti Maryam; Indriyani, Yuni; Nugraha, Eggie; Subaryo, Subaryo (Universitas Muhammadiyah Mataram, 2026)
This research presents an innovative approach to numeracy instruction for pre-service elementary school teachers using holographic images. The primary contribution is the integration of low-cost, mobile-based holographic prototyping within teacher education to enhance spatial reasoning, foster interdisciplinary learning, and support experiential pedagogy. This research aims to analyze prospective teachers' perspectives on holographic media in numeracy learning, with a focus on their experiences in designing and evaluating hologram prototypes for classroom use. A qualitative methodology was adopted, involving 59 pre-service teachers from an elementary teacher education program. Data collection utilized questionnaires and semi-structured interviews, with thematic analysis employed to identify key patterns and themes. Participants engaged in an iterative design process, developing and testing several holographic prototypes, which resulted in a truncated pyramid configuration optimized for mobile-based projection. The analysis identified four principal themes: interdisciplinary applicability, pedagogical strategies for young learners, development of holographic problem-solving skills, and improved spatial–structural understanding. The findings suggest that holographic learning activities enhance student engagement, deepen conceptual understanding, and strengthen both spatial and collaborative skills. This study extends the literature on numeracy and STEM education by illustrating the effective integration of immersive holographic media into pre-service teacher training as a practical and pedagogically valuable instructional innovation.